Optimalisasi Sumber Daya Manusia dalam Dakwah Islam: Perspektif Manajemen Talenta: Optimization of Human Resources in Islamic Da'wah: A Talent Management Perspective - Azwar, Azwar; Muhammad Yusram; Muhammad, Muhammad (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to explore Islamic principles that emphasize the strategic management of individual potential, as exemplified in the lives of Prophet Muhammad (peace be upon him) and his companions. Additionally, the study seeks to develop an effective talent management strategy that aligns with each individual's unique abilities and potential, ensuring that da'wah activities become more effective, efficient, and sustainable. A descriptive qualitative approach is employed to examine and analyze the integration of Islamic principles with modern management strategies in the context of talent management within da'wah organizations. The findings reveal that Islamic principles encourage every individual to recognize, develop, and manage the potential bestowed upon them by Allah, as emphasized in various Quranic verses and hadiths of the Prophet, which highlight the importance of maximizing one's abilities for the benefit of the ummah. Furthermore, this study identifies key strategies for talent management in da'wah, including potential-based recruitment, competency-based placement, continuous training, performance evaluation, the utilization of digital technology, the creation of a conducive work environment, and the enhancement of collaboration within da'wah efforts.